The Economics of futures trading : readings - Goss, B. A.; Yamey, Basil S. (London : Macmillan, 1976)
Several of the major futures markets of today have been established for about a century or longer.
Includes indexes.
Bibliography: p. 225-232.
II 16/01/2019
Loans
Keywords: Futures; Commodity exchanges